A monoclonal antibody that neutralizes SARS-CoV-2 variants, SARS-CoV, and other sarbecoviruses. Issue 1 (31st December 2022) - Wang, Pengfei; Casner, Ryan G.; Nair, Manoj S.; Yu, Jian; Guo, Yicheng; Wang, Maple; Chan, Jasper F.-W.; Cerutti, Gabriele; Iketani, Sho; Liu, Lihong; Sheng, Zizhang; Chen, Zhiwei; et al.
ABSTRACT: The repeated emergence of highly pathogenic human coronaviruses as well as their evolving variants highlight the need to develop potent and broad-spectrum antiviral therapeutics and vaccines. By screening monoclonal antibodies (mAbs) isolated from COVID-19-convalescent patients, we found one mAb, 2-36, with cross-neutralizing activity against SARS-CoV. We solved the cryo-EM structure of 2–36 in complex with SARS-CoV-2 or SARS-CoV spike, revealing a highly conserved epitope in the receptor-binding domain (RBD). Antibody 2–36 neutralized not only all current circulating SARS-CoV-2 variants and SARS-COV, but also a panel of bat and pangolin sarbecoviruses that can use human angiotensin-converting enzyme 2 (ACE2) as a receptor. We selected 2-36-escape viruses in vitro and confirmed that K378 T in SARS-CoV-2 RBD led to viral resistance. Taken together, 2–36 represents a strategic reserve drug candidate for the prevention and treatment of possible diseases caused by pre-emergent SARS-related coronaviruses. Its epitope defines a promising target for the development of a pan-sarbecovirus vaccine.